Preparation method and application of slow-release antibacterial fiber membrane based on Janus structure
By using the chitosan/polylactic acid/zein nanofiber membrane prepared by electrospinning technology in the field of food packaging, the problem of Janus antibacterial film being weakly bonded and the release of antibacterial agents being uncontrollable has been solved, achieving high efficiency and stability. antibacterial effect.
Patent Information
- Application Number
- CN202411465498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-21
AI Technical Summary
In the prior art, the membranes on both sides of the Janus antibacterial membrane are not strongly bound, the rate of antibacterial agent release is uncontrollable, and the biological activity of antibacterial agents has a great impact, resulting in poor application effect in the field of food packaging.
Chitosan/polylactic acid/zein nanofiber membranes are prepared using double-needle parallel electrospinning or needleless electrospinning. The bonding force of the membrane is enhanced through electrospinning technology and heat treatment, and CUR@ β-CD ICs serve as active loading layers to control the release of curcumin.
It significantly enhanced the binding force of the two membranes on both sides of the Janus, achieved a stable antibacterial effect, and extended the antibacterial time through the slow release mechanism to avoid the negative effects of the biological activity of the antibacterial agent.
Smart Images

Figure BDA0005093175780000081 
Figure BDA0005093175780000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food packaging, and relates to a preparation method and application of a slow-release antibacterial fiber film based on a Janus structure. Background Art
[0002] Petroleum-based plastics and their derived packaging materials are widely used in modern society due to their advantages such as low cost, strong plasticity, and superior mechanical properties. However, petroleum is a non-renewable resource. The mass production of petroleum-based plastics and their packaging materials consumes a lot of resources, and there are problems such as difficulty in degradation in the natural environment and the release of harmful substances when heated or exposed to certain environments. Therefore, it is necessary to develop environmentally friendly packaging materials that are renewable and biodegradable.
[0003] Bio-based materials, such as chitosan, polylactic acid, zein, etc., are also preferred raw materials for preparing packaging materials due to their excellent film-forming properties and certain mechanical properties. However, single raw materials often have problems such as poor barrier properties and limited mechanical properties after film formation. Therefore, Janus film, as an emerging concept of membrane material, came into being. It has asymmetric morphology, structure or chemical composition, which makes it have some unique properties that are superior to other membrane materials, and has great application potential in the field of food packaging materials.
[0004] At present, the Janus antibacterial film used in the field of food packaging is mostly prepared by casting. Although the preparation method is simple, the prepared Janus film has the problem that the bonding force of the two sides of the film is not strong and it is easy to peel or delaminate. For example, patent application CN117924779A discloses a chitosan / zein sustained-release antibacterial film with a Janus structure, a preparation method and application. The preparation method is to use polyphenol-plant essential oil Pickering emulsion as a delivery carrier for active substances, chitosan and zein as raw materials, and perform multi-layer casting in a film-forming container, and prepare it by a drying process. This method has a simple process and low cost, but there are problems such as weak bonding of the two sides of the film and easy slippage.
[0005] Inspired by the surface characteristics of lotus leaves, the prior art discloses the use of sequential electrospinning to prepare a three-layer Janus nanofiber membrane having a hydrophilic nanofiber layer (PAN) and a hydrophobic nanofiber middle layer (PVDF). Although this preparation method can prepare nanofiber layers with different properties, the interface between the hydrophilic layer (PAN) and the hydrophobic layer (PVDF) in the prepared three-layer Janus nanofiber membrane still has insufficient adhesion or uneven bonding, resulting in interlayer slippage or separation of the three-layer Janus nanofiber membrane during use, and it is also easily contaminated in actual use, resulting in performance degradation and structural damage.
[0006] In addition, the prior art also discloses the use of a double electrospinning method to prepare a three-layer Janus nanofiber membrane. However, although the double electrospinning method can spin different solutions on different nozzles to prepare films with different properties on both sides, it is often difficult to effectively enhance the bonding force between the two sides of the membrane and between the membrane and the substrate, especially during use, it is easy to cause structural instability or insufficient durability.
[0007] In addition to the problem of the firmness of the bonding between the two sides of the Janus film, its antibacterial properties and sustained-release properties need to be considered when used in the field of food packaging. However, in the prior art, there are problems such as the uncontrollable release rate of the antibacterial agent and the significant influence of the packaging material preparation method on the biological activity of the antibacterial agent.
[0008] Therefore, it is of great significance to study a preparation method and application of a sustained-release antibacterial fiber membrane based on Janus structure to solve the above problems. Summary of the invention
[0009] The purpose of the present invention is to solve the problems existing in the prior art and to provide a method for preparing a chitosan / polylactic acid / zein sustained-release antibacterial film based on a Janus structure and its application for food preservation.
[0010] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing a slow-release antibacterial fiber membrane based on a Janus structure, using a chitosan (CS) / polylactic acid (PLA) nanofiber membrane as a receiving substrate, using a double-needle parallel electrospinning method or a needle-free electrospinning method, spinning a positively charged spinning solution A and a negatively charged spinning solution B to obtain an electrospun fiber membrane, and the electrospun fiber membrane is vacuum dried, heat treated (heat treated at a temperature of 120 to 160° C. for 10 to 15 minutes), and cut to shape to obtain a slow-release antibacterial fiber membrane based on a Janus structure;
[0012] The positively charged spinning solution A is obtained by adding the positively charged solution to the CUR@β-CD ICs / CS / PLA spinning solution, and the negatively charged spinning solution B is obtained by adding the negatively charged solution to the zein spinning solution; or, the positively charged spinning solution A is obtained by adding the positively charged solution to the zein spinning solution, and the negatively charged spinning solution B is obtained by adding the negatively charged solution to the CUR@β-CD ICs / CS / PLA spinning solution;
[0013] The CUR@β-CD ICs / CS / PLA spinning solution was obtained by dissolving curcumin / β-cyclodextrin inclusion complex (CUR@β-CD ICs), chitosan and polylactic acid in a solvent.
[0014] The zein used in the present invention is a plant protein and also a film-forming material, which can be extracted from corn. The zein molecule itself contains abundant polar groups and hydrophilic functional groups, which can interact with water molecules to reduce water permeability. This property enables zein to be used as a natural moisture barrier agent, so the Zein film has good moisture barrier and gas barrier properties, and the Zein film can be degraded under natural conditions, has no pollution to the environment, and is a green and safe material.
[0015] The present invention utilizes electrospinning technology to prepare a CUR@β-CD ICs / CS / PLA nanofiber membrane as an active loading layer. The nanofiber membrane has a large specific surface area and a high porosity, and can respond to humidity stimulation in a packaging environment, thereby controlling the accurate release of curcumin at a specific position, and has broad application prospects in the field of active food packaging.
[0016] In order to solve the problem of weak bonding between the two sides of the Janus antibacterial membrane in the prior art, the first preparation scheme of the slow-release antibacterial fiber membrane based on the Janus structure provided by the present invention realizes the cross-entanglement of the fibers by spinning the CUR@β-CD ICs / CS / PLA spinning solution and the Zein spinning solution, and significantly enhances the bonding firmness between the two layers of fiber membranes. The unfolding of the zein polypeptide chain will expose the tyrosine residues, and the amino and carboxyl groups of the tyrosine residues can form hydrogen bonds, while the chitosan molecular chain contains amino, carboxyl and other groups. Zein and chitosan can be associated through electrostatic interactions, hydrogen bonds, hydrophobic interactions, etc., so that the intermolecular forces between the two are enhanced. The present invention makes full use of the intermolecular interactions between zein and chitosan, and further enhances the bonding force between the fiber membranes. In order to further enhance the stability and durability of the fiber membrane, the present invention also adds substances with different electrical properties to the two spinning solutions used for spinning, and through the principle of opposites attract, a certain bonding force is given to the two films after spinning, and the adhesion of the zein film to the substrate is enhanced, so that the bonding between the two films and between the two films and the substrate is more firm, and the shape can be well maintained when subjected to external forces during transportation, etc., to prevent the films on both sides from slipping and breaking. In addition, by heat treatment after electrospinning, hot melt bonding can occur between the molecules of different materials in the composite film, thereby further increasing the bonding force of the composite film.
[0017] As the preferred technical solution:
[0018] The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure as described above, the specific preparation process of the CUR@β-CD ICs / CS / PLA spinning solution is as follows: adding curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid to an acetic acid solution with a volume concentration of 60%, heating and stirring at 50-60° C. for 4-6 hours to obtain the CUR@β-CD ICs / CS / PLA spinning solution;
[0019] The total amount of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid is 16-20% by mass / volume relative to the acetic acid solution; based on the total mass of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of curcumin / β-cyclodextrin inclusion complex is 2-5%, the mass proportion of chitosan is 85-90%, and the mass proportion of polylactic acid is 5-10%.
[0020] The specific preparation process of the curcumin / β-cyclodextrin inclusion complex is as follows: first, β-cyclodextrin is prepared into an aqueous solution, curcumin is dissolved in ethanol to prepare a curcumin ethanol solution, and then the curcumin ethanol solution is added to the β-cyclodextrin aqueous solution, stirred at a temperature of 30 to 35° C. for 2.0 to 2.7 hours, and then frozen centrifuged to obtain inclusion complex powder, and excess impurities are washed away to obtain the curcumin / β-cyclodextrin inclusion complex; wherein the molar ratio of curcumin to β-cyclodextrin is 0.95 to 1.02:1.
[0021] The method for preparing a slow-release antibacterial fiber membrane based on a Janus structure as described above, the specific preparation process of the zein spinning solution is: adding zein to an acetic acid solution with a volume fraction of 70%, adjusting the pH value to 5-7, heating and stirring at 50-60° C. for 1 hour, and obtaining the zein spinning solution;
[0022] The mass / volume percentage of zein relative to the acetic acid solution is 1% to 5% (ie, 1 to 5 g / 100 mL).
[0023] The preparation method of the sustained-release antibacterial fiber membrane based on the Janus structure as described above, the specific preparation process of the chitosan / polylactic acid nanofiber membrane is: chitosan and polylactic acid are added to a mixed solution of dichloromethane and N, N-dimethylformamide to obtain a spinning solution, and the chitosan / polylactic acid nanofiber membrane is prepared by an electrospinning method;
[0024] The mass ratio of chitosan to polylactic acid is 70-90:10-30; the mass / volume percentage of the total amount of chitosan and polylactic acid relative to the mixed solution of dichloromethane and N,N-dimethylformamide is 5-7%; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:3;
[0025] The process parameters of double-needle parallel electrospinning are: voltage of 18-24 kV, needle specification of 22G, distance between positive and negative electrodes of 15-20 cm, spinning speed of 1.6-1.8 mL / h, roller speed of 200 rpm, spinning environment temperature of 22-25 ° C, and ambient humidity of 25-40% RH.
[0026] The process parameters of needle-free electrospinning were as follows: the coil spinneret was 20 cm long and 8 cm in diameter, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm to reduce the effect of electrostatic repulsion, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0027] The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure as described above, wherein the positively charged solution is a 1 mM hexadecyltrimethylammonium bromide (CTAB) aqueous solution, and the CTAB powder is added to water preheated to 40-50° C. and stirred until completely dissolved;
[0028] The negatively charged solution is an aqueous solution of negatively charged metal nanoparticles; the mass fraction of the aqueous solution of negatively charged metal nanoparticles is 1%; the metal nanoparticles are gold nanoparticles, silver nanoparticles, zinc oxide nanoparticles, ferrite (such as Fe3O4) nanoparticles or titanium dioxide (TiO2) nanoparticles; the metal nanoparticles are formed by dissolving a metal salt or a metal precursor in water, ethanol or acetone and then adding the metal salt or metal precursor to a reducing agent or a precipitant; for silver nanoparticles and gold nanoparticles, commonly used reducing agents are hydrogen, sodium borohydride (NaBH4) or citric acid; for zinc oxide nanoparticles, commonly used precipitants are dilute acids (such as nitric acid), sodium hydroxide solutions (used under alkaline conditions) or other organic solvents; for ferrite nanoparticles and titanium dioxide nanoparticles, they are usually synthesized by appropriate precipitation methods or hydrothermal methods; finally, appropriate ultrasonic treatment or stirring is performed to ensure that the nanoparticles are uniformly dispersed in the aqueous solution and maintain stability;
[0029] For gold, silver, and titanium dioxide nanoparticles, the surface of the metal nanoparticles will adsorb negative ions or organic matter (such as chloride ions or organic molecules), causing them to be negatively charged; zinc oxide nanoparticles will form zinc oxide surfaces in aqueous solutions and react with ions in the water to form negatively charged ZnO nanoparticles; ferrite nanoparticles (such as Fe3O4) will be negatively charged in water due to the hydroxides or other reactive substances on their surfaces.
[0030] The volume percentage of the positively charged solution or the negatively charged solution added to the CUR@β-CD ICs / CS / PLA spinning solution or the zein spinning solution is 1% to 2%.
[0031] The process parameters of the double-needle parallel electrospinning of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage of 16-22 kV, needle specification of 20 G, distance between the positive and negative electrodes of 15-20 cm, spinning speed of 0.5-1.0 mL / h, roller speed of 200 rpm, spinning environment temperature of 22-25 °C, and environment humidity of 25-40% RH;
[0032] The needleless electrospinning process parameters of CUR@β-CD ICs / CS / PLA nanofibrous membrane were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm to reduce the effect of electrostatic repulsion, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0033] The process parameters of double-needle parallel electrospinning of zein film are as follows: voltage of 16-22 kV, needle specification of 20G, distance between positive and negative electrodes of 15-20 cm, spinning speed of 0.5-1.0 mL / h, roller speed of 200 rpm, spinning environment temperature of 22-25°C, and environment humidity of 25-40% RH.
[0034] The needle-free electrospinning process parameters of zein film were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm to reduce the effect of electrostatic repulsion, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0035] The present invention also provides a method for preparing a slow-release antibacterial fiber membrane based on a Janus structure, wherein a petal-shaped nano ZnO fiber membrane is used as a receiving substrate, a double-needle parallel electrospinning method or a needle-free electrospinning method is adopted, a positively charged spinning solution C and a positively charged spinning solution D are spun to obtain an electrospun fiber membrane, and the electrospun fiber membrane is vacuum dried, heat treated (the heat treatment temperature is 120 to 160° C., and the time is 10 to 15 minutes), and cut to shape to obtain a slow-release antibacterial fiber membrane based on a Janus structure;
[0036] The petal-shaped nano ZnO fiber membrane is prepared by electrochemical deposition (ECD) method with zinc foil as the substrate to form a super-hydrophobic surface and achieve a more effective water-isolating effect;
[0037] The electrolyte used in electrochemical deposition is a mixture of (NH4)2SO4 solution, ZnSO4 solution and NaOH solution, and the pH value of the electrolyte is 7.5 to 9.5;
[0038] The preparation process of the electrochemical deposition method is: controlling the following factors during the electrodeposition process can ensure that the petal-shaped nano ZnO fiber membrane is necessarily negatively charged: ① Higher pH value: ZnO will show negative charge in an alkaline environment, so it can be deposited at a higher pH value to promote the negative charge of the ZnO film. ② Electrolyte composition: Electrolytes containing a higher concentration of negative ions (such as sulfate or chloride, the present invention selects (NH4)2SO4) can promote the formation of negative charges on the ZnO surface. These ions may be adsorbed to the ZnO surface, increasing its negative charge density;
[0039] The specific preparation steps of the petal-shaped nano ZnO fiber membrane are as follows:
[0040] (1) Use 1M hydrochloric acid to treat a 1cm×1c m The zinc foil is cleaned to remove the passive oxidation layer on the zinc foil, and then fully cleaned with deionized water (DI);
[0041] (2) stirring a 2M (NH4)2SO4 aqueous solution and a 0.1M ZnSO4 aqueous solution in a magnetic stirrer for 20 minutes to ensure uniform mixing, and then adding a 1M NaOH aqueous solution and continuing to stir for 10 minutes to make its pH value 7.5-9.5 to ensure that the electrodeposition process is in a slightly alkaline state, that is, the electrolyte; wherein the mass ratio of (NH4)2SO4, ZnSO4 and NaOH is 16.4:1:2.5;
[0042] (3) The electrolyte is placed in a non-isolated beaker and the non-isolated beaker is placed in an electrodeposition tank. Then, a zinc foil is used as a working electrode and a platinum rod is used as a counter electrode in the non-isolated beaker for electrodeposition. The distance between the two electrodes is 1 cm. Finally, the deposited film is taken out of the bath, thoroughly washed with deionized water, and dried in a vacuum oven for 24 hours to obtain a petal-shaped nano ZnO fiber film. The current density of the electrodeposition is 0.5 A cm -2 The deposition process is divided into three stages. The deposition time of the three stages is 200s, 300s, and 400s respectively, and the interval between each stage is 5min.
[0043] The positively charged spinning solution C was obtained by adding the positively charged solution to the CUR@β-CD ICs / CS / PLA spinning solution, and the positively charged spinning solution D was obtained by adding the positively charged solution to the zein spinning solution;
[0044] The CUR@β-CD ICs / CS / PLA spinning solution was obtained by dissolving curcumin / β-cyclodextrin inclusion complex (CUR@β-CD ICs), chitosan and polylactic acid in a solvent.
[0045] In order to solve the problem of weak bonding between the two sides of the Janus antibacterial membrane in the prior art, the second preparation scheme of the sustained-release antibacterial fiber membrane based on the Janus structure provided by the present invention uses a petal-shaped nano ZnO fiber membrane as a receiving substrate, and adopts a double-needle parallel electrospinning method to spin the CUR@β-CD ICs / CS / PLA spinning solution and the Zein spinning solution, and positively charged substances are added to the two spinning solutions for spinning, so as to combine with the negatively charged receiving substrate, and enhance the adhesion of the zein membrane and the CUR@β-CD ICs / CS / PLA membrane to the substrate through the principle of opposites attracting, so that the bonding between the two films and the substrate is more firm. In addition, the present invention innovatively uses the electrodeposition method to generate a petal-shaped nanostructure on the surface of the zinc foil, which increases the surface roughness and hydrophobic effect, cooperates with the moisture-proof effect of the outermost zein membrane, and better achieves the water-proof effect; moreover, due to the Zn 2+ It is easy to diffuse into the biofilm (i.e., the biofilm formed by bacteria). Zn diffused into the biofilm 2+ , can interfere with bacterial enzyme activity, inhibit protein synthesis, and destroy bacterial cell membrane structure, so that the obtained slow-release antibacterial fiber film has a more excellent antibacterial effect. Therefore, the slow-release antibacterial fiber film based on Janus structure prepared by the present invention can be well used in the field of food packaging materials.
[0046] As the preferred technical solution:
[0047] The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure as described above, the specific preparation process of the CUR@β-CD ICs / CS / PLA spinning solution is as follows: adding curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid to an acetic acid solution with a volume concentration of 60%, heating and stirring at 50-60° C. for 4-6 hours to obtain the CUR@β-CD ICs / CS / PLA spinning solution;
[0048] The total amount of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid is 16-20% by mass / volume relative to the acetic acid solution; based on the total mass of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of curcumin / β-cyclodextrin inclusion complex is 2-5%, the mass proportion of chitosan is 85-90%, and the mass proportion of polylactic acid is 5-10%.
[0049] The specific preparation process of the curcumin / β-cyclodextrin inclusion complex is as follows: first, β-cyclodextrin is prepared into an aqueous solution, curcumin is dissolved in ethanol to prepare a curcumin ethanol solution, and then the curcumin ethanol solution is added to the β-cyclodextrin aqueous solution, stirred at a temperature of 30 to 35° C. for 2.0 to 2.7 hours, and then frozen centrifuged to obtain inclusion complex powder, and excess impurities are washed away to obtain the curcumin / β-cyclodextrin inclusion complex; wherein the molar ratio of curcumin to β-cyclodextrin is 0.95 to 1.02:1.
[0050] The method for preparing a slow-release antibacterial fiber membrane based on a Janus structure as described above, the specific preparation process of the zein spinning solution is: adding zein to an acetic acid solution with a volume fraction of 70%, adjusting the pH value to 5-7, heating and stirring at 50-60° C. for 1 hour, and obtaining the zein spinning solution;
[0051] The mass / volume percentage of zein relative to the acetic acid solution is 1% to 5%.
[0052] In the method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, the positively charged solution is a solution with a concentration of 1 mM obtained by dissolving PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-doped polystyrene sulfonate) powder in water;
[0053] The volume percentage of the positively charged solution relative to the CUR@β-CD ICs / CS / PLA spinning solution or the zein spinning solution is 1% to 2%.
[0054] The process parameters of the double-needle parallel electrospinning of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage of 16-22 kV, needle specification of 20 G, distance between the positive and negative electrodes of 15-20 cm, spinning speed of 0.5-1.0 mL / h, roller speed of 200 rpm, spinning environment temperature of 22-25 °C, and environment humidity of 25-40% RH;
[0055] The needleless electrospinning process parameters of CUR@β-CD ICs / CS / PLA nanofibrous membrane were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm to reduce the effect of electrostatic repulsion, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0056] The process parameters of double-needle parallel electrospinning of zein film are as follows: voltage of 16-22 kV, needle specification of 20G, distance between positive and negative electrodes of 15-20 cm, spinning speed of 0.5-1.0 mL / h, roller speed of 200 rpm, spinning environment temperature of 22-25°C, and environment humidity of 25-40% RH.
[0057] The needle-free electrospinning process parameters of zein film were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm to reduce the effect of electrostatic repulsion, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0058] The present invention also provides the application of the slow-release antibacterial fiber membrane based on Janus structure prepared by any of the preparation methods described above for food preservation.
[0059] Beneficial effects:
[0060] (1) The present invention innovatively utilizes the principle of attraction between opposite charges and significantly enhances the bonding force between the two films and the substrate through a specific treatment method, thereby effectively solving the problem of weak bonding between the two films in the prior art, and has significant application potential and technical advantages;
[0061] (2) The electrospinning technology used in the present invention has mild operating conditions, will not damage the biological activity of curcumin, and has low cost and simple process;
[0062] (3) The CUR@β-CD ICs / CS / PLA nanofiber membrane prepared by electrospinning technology in the present invention is an active loading layer. The nanofiber membrane has a large specific surface area and high porosity, and can respond to humidity stimulation in the packaging environment, thereby controlling the accurate release of curcumin at a specific location, and has broad application prospects in the field of food active packaging;
[0063] (4) Since curcumin is a natural antibacterial agent with broad-spectrum antibacterial properties, the nanofiber membrane loaded with curcumin inclusion complex prepared by the present invention has good antibacterial properties and is gradually released through a sustained-release mechanism to ensure a long-term antibacterial effect; in addition, the present invention uses a natural antibacterial agent to be added to the active food packaging material, which will not affect human health. DETAILED DESCRIPTION
[0064] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0065] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0066] Elongation at break and breaking strength: The sustained-release antibacterial fiber membrane based on the Janus structure prepared in each embodiment and comparative example was first cut into samples of 10 mm × 100 mm in size, and then a universal tensile testing machine (Jinan Hengxu Co., Ltd.) was used to test the elongation at break and the breaking strength of the samples; wherein the stretching rate was 200 mm / min.
[0067] Water vapor permeability and oxygen permeability: refer to GB / T 1037-2021 "Determination of water vapor permeability of plastic films and sheets by cup weight gain and weight loss method" standard to test the sustained-release antibacterial fiber membrane based on Janus structure prepared in each embodiment and comparative example, fix the sustained-release antibacterial fiber membrane based on Janus structure at the mouth of a centrifuge tube with a specification of 50mL, the opening diameter of the centrifuge tube is 26.5mm, and 20.0±0.5g of anhydrous silica gel and 20.0±0.5g of deoxygenation bag are respectively loaded into the centrifuge tube, and then the mass change of the centrifuge tube is continuously recorded under the conditions of 75% RH humidity and 25°C until the 7th day, and then accurately weighed, and then the water vapor permeability and oxygen permeability are calculated according to the formula;
[0068] The water vapor transmission rate calculation formula is as follows:
[0069]
[0070] In the formula, Δm represents the mass difference before and after the centrifuge tube, e represents the thickness of the membrane, t represents the measurement time, A represents the area of the centrifuge tube mouth, and Δp represents the vapor pressure at 25°C;
[0071] The calculation formula of oxygen transmission rate is as follows:
[0072]
[0073] Where Δm represents the mass difference before and after the centrifuge tube, t represents the measurement time, and A represents the area of the centrifuge tube mouth.
[0074] Colony count of Escherichia coli: The standard microbiological detection method (AOAC method) was used, with Gram-negative Escherichia coli (Escherichia coli: ATCC25922) as the representative bacterial model. The OD value of the bacterial solution at 600 nm was measured by an ELISA reader (Spectra MAX19, Meigu Molecular Instrument Co., Ltd.), and then the Escherichia coli stock solution was diluted to 1×10 5 times, and then the sustained-release antibacterial fiber membrane based on Janus structure prepared in each embodiment and comparative example was inoculated into the culture medium, and 100 μL of diluted Escherichia coli stock solution was added thereto, and then it was incubated in a 37°C incubator for 4 h, and the sample without membrane was used as a blank control, and finally 50 μL of the Escherichia coli mixed solution was taken from the culture medium after the above incubation and spread on the solid agar culture medium, and cultured in a 37°C incubator for 24 h to observe the growth of the colonies, and the colonies were counted.
[0075] Colony count of Staphylococcus aureus: Using the standard microbiological detection method (AOAC method), Gram-positive Staphylococcus aureus (ATCC25923) was used as a representative bacterial model. The OD value of Staphylococcus aureus at 600 nm was first measured by an ELISA reader (Spectra MAX19, Meigu Molecular Instrument Co., Ltd.), and then Staphylococcus aureus was diluted to 1×10 5 times, and then inoculated the sustained-release antibacterial fiber membrane based on the Janus structure prepared in each embodiment and comparative example into the culture medium, and then added 100 μL of the diluted Staphylococcus aureus thereto, and then incubated it in a 37°C incubator for 4 h, and used the sample without membrane as a blank control, and finally took 50 μL of the Staphylococcus aureus mixture from the culture medium after the above incubation and spread it on the solid agar culture medium, and incubated it in a 37°C incubator for 24 h to observe the growth of the colonies, and counted the colonies.
[0076] Antibacterial rate: The slow-release antibacterial fiber membranes based on the Janus structure prepared in each embodiment and comparative example were tested according to the standard antibacterial test method AATCC 100, and the antibacterial performance of the nanofiber membranes was evaluated by the plate colony counting method.
[0077] Release amount of curcumin: The basement membrane and the side membrane of the sustained-release antibacterial fiber membrane based on the Janus structure prepared in each embodiment and comparative example were first separated, and then the concentration of curcumin in each layer was measured according to GB 31604.8-2021 "Determination of the total migration amount of food contact materials and articles of national food safety standard" (PBS buffer solution (pH = 7.0) was selected as the common food simulation solution, and the measurement was carried out at 4 ° C), and then the release amount was calculated according to the measured concentration and sampling volume by the calculation formula, and the calculation formula is as follows:
[0078] Released Amount=(C t ×V×D)-(C0×V×D);
[0079] In the formula, C t is the curcumin concentration at time t (mg / L), C0 is the initial concentration (mg / L), V is the sampling volume (L), and D is the dilution factor.
[0080] Weight loss rate: The sustained-release antibacterial fiber membrane based on the Janus structure prepared in each embodiment and comparative example was used as a sample and tested at a temperature of 25°C and a relative humidity of 60% for 4 days. The initial mass and the mass after 96 hours of treatment were recorded by weighing method, and the weight loss rate was calculated by the calculation formula: (initial mass-mass after treatment) / initial mass×100%.
[0081] Example 1
[0082] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0083] (1) Preparation of raw materials;
[0084] β-cyclodextrin;
[0085] water;
[0086] Curcumin;
[0087] Ethanol;
[0088] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0089] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0090] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0091] Hexadecyltrimethylammonium bromide;
[0092] Metal salt: chloroauric acid (HAuCl4);
[0093] Reducing agent: prepare sodium borohydride and water into a sodium borohydride solution with a concentration of 0.1M;
[0094] Dichloromethane;
[0095] N,N-dimethylformamide;
[0096] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0097] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 30° C. for 2.7 h, and then freezing centrifuging to obtain an inclusion compound powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion compound; wherein the molar ratio of curcumin to β-cyclodextrin is 0.95:1;
[0098] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid prepared in step (2.1) to an acetic acid aqueous solution with a volume concentration of 60%, and heating and stirring at 50° C. for 6 hours to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid aqueous solution is 16%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 5%, the mass proportion of chitosan is 85%, and the mass proportion of the polylactic acid is 10%;
[0099] (3) preparing a zein spinning solution;
[0100] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 7, heating and stirring at 60° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 5%;
[0101] (4) preparing an aqueous solution of hexadecyltrimethylammonium bromide and an aqueous solution of negatively charged metal nanoparticles;
[0102] (4.1) preparing a hexadecyltrimethylammonium bromide aqueous solution;
[0103] Adding hexadecyltrimethylammonium bromide powder into water preheated to 50° C. and stirring until completely dissolved, thereby obtaining a hexadecyltrimethylammonium bromide aqueous solution with a concentration of 1 mM;
[0104] (4.2) preparing an aqueous solution of negatively charged metal nanoparticles;
[0105] After dissolving the metal salt in water at a mass ratio of 1:15, a reducing agent is added thereto and stirred to make it uniformly dispersed, and then citric acid is added thereto and reacted at 70°C and 760 mmHg for 2 hours to form gold nanoparticles, and then cooled to 25°C and added to water to make the gold nanoparticles uniformly dispersed in the water by ultrasonic treatment, so as to obtain a 1% aqueous solution of negatively charged metal nanoparticles; wherein the amount of citric acid added is 6% of the amount of the metal salt added, and the mass ratio of the metal salt to the reducing agent is 1:7;
[0106] (5) preparing a positively charged spinning solution A and a negatively charged spinning solution B;
[0107] Adding a hexadecyltrimethylammonium bromide aqueous solution to a zein spinning solution to obtain a positively charged spinning solution A; wherein the volume percentage of the hexadecyltrimethylammonium bromide aqueous solution relative to the zein spinning solution is 2%;
[0108] Adding a negatively charged metal nanoparticle aqueous solution to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a negatively charged spinning solution B; wherein the volume percentage of the negatively charged metal nanoparticle aqueous solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 1%;
[0109] (6) preparing chitosan / polylactic acid nanofiber membrane;
[0110] Chitosan and polylactic acid are added to a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a spinning solution, and a chitosan / polylactic acid nanofiber membrane is prepared by a double-needle parallel electrospinning method; wherein the mass ratio of chitosan to polylactic acid is 70:30; the total amount of chitosan and polylactic acid relative to the mass / volume percentage of the mixed solution of dichloromethane and N,N-dimethylformamide is 7%; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:3;
[0111] The electrospinning process parameters were: voltage 18 kV, needle gauge 22 G, distance between positive and negative electrodes 15 cm, spinning speed 1.8 mL / h, roller speed 200 rpm, spinning environment temperature 22 °C, and environment humidity 40% RH;
[0112] (7) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0113] The chitosan / polylactic acid nanofiber membrane obtained in step (6) is used as a receiving substrate, and the positively charged spinning solution A and the negatively charged spinning solution B obtained in step (4) are spun on both sides of the receiving substrate by a double-needle parallel electrospinning method to form a CUR@β-CD ICs / CS / PLA nanofiber membrane and a zein membrane, and then vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on a Janus structure; wherein the heat treatment temperature is 160° C. and the time is 10 min;
[0114] The spinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage 22 kV, needle gauge 20 G, distance between positive and negative electrodes 20 cm, spinning speed 0.8 mL / h, roller speed 200 rpm, spinning environment temperature 22 °C, and environment humidity 34% RH;
[0115] The spinning process parameters of the zein film are: voltage of 22 kV, needle specification of 20G, distance between the positive electrode and the negative electrode of 20 cm, spinning speed of 1 mL / h, roller speed of 200 rpm, spinning environment temperature of 25°C, and environment humidity of 40% RH.
[0116] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the sustained-release antibacterial fiber membrane based on Janus structure was 58 μm, the thickness of the zein membrane was 155 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 234 μm. The elongation at break of the sustained-release antibacterial fiber membrane based on Janus structure was 40.7%, the breaking strength was 7.3 MPa, and the water vapor permeability was 7.5×10 -11 g / ms Pa, oxygen permeability is 6.9×10 -5 g / m 2 s, the colony count of Escherichia coli was 11 CFU, the colony count of Staphylococcus aureus was 17 CFU, the antibacterial rate of Escherichia coli was 98.43%, the antibacterial rate of Staphylococcus aureus was 97.85%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.17 nL / cm 2 The release rate of curcumin in zein film was 0.1nL / cm 2 .
[0117] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0118] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0119] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber membrane based on the Janus structure is 14.43%, indicating that the slow-release antibacterial fiber membrane based on the Janus structure can reduce the loss of water in fresh fruits and vegetables in the package, thereby delaying the loss of water and maintaining freshness.
[0120] Example 2
[0121] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0122] (1) Preparation of raw materials;
[0123] β-cyclodextrin;
[0124] water;
[0125] Curcumin;
[0126] Ethanol;
[0127] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0128] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0129] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0130] Hexadecyltrimethylammonium bromide;
[0131] Metal salt: silver nitrate (AgNO3);
[0132] Reducing agent: citric acid;
[0133] Dichloromethane;
[0134] N,N-dimethylformamide;
[0135] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0136] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 32° C. for 2.4 h, and then freezing centrifuging to obtain an inclusion complex powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion complex; wherein the molar ratio of curcumin to β-cyclodextrin is 0.98:1;
[0137] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid obtained in step (2.1) to an acetic acid aqueous solution with a volume concentration of 60%, and heating and stirring at 55° C. for 5 h to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid aqueous solution is 18%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 2%, the mass proportion of chitosan is 90%, and the mass proportion of the polylactic acid is 8%;
[0138] (3) preparing a zein spinning solution;
[0139] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 6, heating and stirring at 55° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 3%;
[0140] (4) preparing an aqueous solution of hexadecyltrimethylammonium bromide and an aqueous solution of negatively charged metal nanoparticles;
[0141] (4.1) preparing a hexadecyltrimethylammonium bromide aqueous solution;
[0142] Adding hexadecyltrimethylammonium bromide powder into water preheated to 45° C. and stirring until completely dissolved, thereby obtaining a hexadecyltrimethylammonium bromide aqueous solution with a concentration of 1 mM;
[0143] (4.2) preparing an aqueous solution of negatively charged metal nanoparticles;
[0144] The metal salt is dissolved in water at a mass ratio of 1:15, and then added to a reducing agent to react for 2 hours at 70°C and 760 mmHg to form silver nanoparticles, and then cooled to 25°C and added to water, and finally stirred to uniformly disperse the silver nanoparticles in water to obtain a negatively charged titanium dioxide nanoparticle aqueous solution with a mass fraction of 1%; wherein the mass ratio of the metal salt to the reducing agent is 1:5;
[0145] (5) preparing a positively charged spinning solution A and a negatively charged spinning solution B;
[0146] A hexadecyltrimethylammonium bromide aqueous solution is added to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a positively charged spinning solution A; wherein the volume percentage of the hexadecyltrimethylammonium bromide aqueous solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 1%;
[0147] Adding a negatively charged metal nanoparticle aqueous solution to a zein spinning solution to obtain a negatively charged spinning solution B; wherein the volume percentage of the negatively charged metal nanoparticle aqueous solution relative to the zein spinning solution is 2%;
[0148] (6) preparing chitosan / polylactic acid nanofiber membrane;
[0149] Chitosan and polylactic acid are added to a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a spinning solution, and a chitosan / polylactic acid nanofiber membrane is prepared by a needleless electrospinning method; wherein the mass ratio of chitosan to polylactic acid is 75:25; the total amount of chitosan and polylactic acid is 6% by mass / volume relative to the mixed solution of dichloromethane and N,N-dimethylformamide; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:3;
[0150] The needle-free electrospinning process parameters of chitosan / PLA nanofiber membranes were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm, the collection distance was set to 25 cm, and the production line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%;
[0151] (7) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0152] The chitosan / polylactic acid nanofiber membrane obtained in step (6) is used as a receiving substrate, and the positively charged spinning solution A and the negatively charged spinning solution B obtained in step (4) are spun on both sides of the receiving substrate by a needle-free electrospinning method to form a CUR@β-CD ICs / CS / PLA nanofiber membrane and a zein membrane, and then vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on a Janus structure; wherein the heat treatment temperature is 140° C. and the time is 13 min;
[0153] The needleless electrospinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%;
[0154] The process parameters of needle-free electrospinning of zein film were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0155] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the Janus structure-based sustained-release antibacterial fiber membrane was 61 μm, the thickness of the zein membrane was 164 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 255 μm. The elongation at break, the breaking strength, and the water vapor permeability of the Janus structure-based sustained-release antibacterial fiber membrane were 46.2%, 7.6 MPa, and 7.3×10 -11 g / ms Pa, oxygen permeability is 7.1×10 -5 g / m 2 s, the colony count of Escherichia coli was 101 gCFU / g, the colony count of Staphylococcus aureus was 10CFU, the antibacterial rate of Escherichia coli was 98.57%, the antibacterial rate of Staphylococcus aureus was 98.73%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.13 L / cm 2 The release rate of curcumin in zein film was 0.09 L / cm 2 .
[0156] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0157] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0158] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber film based on the Janus structure is 13.07%, indicating that the slow-release antibacterial fiber film based on the Janus structure can reduce the water loss of fresh fruits and vegetables in the package, thereby delaying the water loss and maintaining freshness.
[0159] Example 3
[0160] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0161] (1) Preparation of raw materials;
[0162] β-cyclodextrin;
[0163] water;
[0164] Curcumin;
[0165] Ethanol;
[0166] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0167] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0168] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0169] Hexadecyltrimethylammonium bromide;
[0170] Metal salts: zinc chloride;
[0171] Precipitant: 1M ammonia water;
[0172] Dichloromethane;
[0173] N,N-dimethylformamide;
[0174] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0175] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 35° C. for 2 h, and then freezing centrifuging to obtain an inclusion compound powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion compound; wherein the molar ratio of curcumin to β-cyclodextrin is 1.02:1;
[0176] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid prepared in step (2.1) to an acetic acid aqueous solution with a volume concentration of 60%, and heating and stirring at 60°C for 4 hours to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid aqueous solution is 20%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 5%, the mass proportion of chitosan is 90%, and the mass proportion of the polylactic acid is 5%;
[0177] (3) preparing a zein spinning solution;
[0178] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 5, heating and stirring at 50° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 1%;
[0179] (4) preparing an aqueous solution of hexadecyltrimethylammonium bromide and an aqueous solution of negatively charged metal nanoparticles;
[0180] (4.1) preparing a hexadecyltrimethylammonium bromide aqueous solution;
[0181] Adding hexadecyltrimethylammonium bromide powder into water preheated to 40° C. and stirring until completely dissolved, thereby obtaining a hexadecyltrimethylammonium bromide aqueous solution with a concentration of 1 mM;
[0182] (4.2) preparing an aqueous solution of negatively charged metal nanoparticles;
[0183] The metal salt is dissolved in water at a mass ratio of 1:15, and then added to a precipitant to react at 70°C and 760 mmHg for 2 hours to form zinc oxide nanoparticles, and then cooled to 25°C and added to water, and finally the zinc oxide nanoparticles are uniformly dispersed in water by ultrasonic treatment or stirring to obtain a negatively charged titanium dioxide nanoparticle aqueous solution with a mass fraction of 1%; wherein the mass ratio of the metal salt to the precipitant is 1:3;
[0184] (5) preparing a positively charged spinning solution A and a negatively charged spinning solution B;
[0185] The hexadecyltrimethylammonium bromide aqueous solution is added to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a positively charged spinning solution A; wherein the volume percentage of the hexadecyltrimethylammonium bromide aqueous solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 2%;
[0186] Adding a negatively charged metal nanoparticle aqueous solution to a zein spinning solution to obtain a negatively charged spinning solution B; wherein the volume percentage of the negatively charged metal nanoparticle aqueous solution relative to the zein spinning solution is 1%;
[0187] (6) preparing chitosan / polylactic acid nanofiber membrane;
[0188] Chitosan and polylactic acid are added to a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a spinning solution, and a chitosan / polylactic acid nanofiber membrane is prepared by a double-needle parallel electrospinning method; wherein the mass ratio of chitosan to polylactic acid is 70:30; the mass / volume percentage of the total amount of chitosan and polylactic acid relative to the mixed solution of dichloromethane and N,N-dimethylformamide is 5%; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:3;
[0189] The electrospinning process parameters were: voltage 24 kV, needle gauge 22 G, distance between positive and negative electrodes 20 cm, spinning speed 1.6 mL / h, roller speed 200 rpm, spinning environment temperature 23 °C, and environment humidity 25% RH;
[0190] (7) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0191] The chitosan / polylactic acid nanofiber membrane obtained in step (6) is used as a receiving substrate, and the positively charged spinning solution A and the negatively charged spinning solution B obtained in step (4) are spun on both sides of the receiving substrate by a double-needle parallel electrospinning method to form a CUR@β-CD ICs / CS / PLA nanofiber membrane and a zein membrane, and then vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on a Janus structure; wherein the heat treatment temperature is 120° C. and the time is 15 min;
[0192] The spinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage 16 kV, needle gauge 20 G, distance between positive and negative electrodes 15 cm, spinning speed 0.5 mL / h, roller speed 200 rpm, spinning environment temperature 25 °C, and ambient humidity 40% RH;
[0193] The spinning process parameters of the zein film are: voltage of 16 kV, needle specification of 20 G, distance between the positive electrode and the negative electrode of 15 cm, spinning speed of 0.5 mL / h, roller speed of 200 rpm, spinning environment temperature of 22° C., and environment humidity of 25% RH.
[0194] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the sustained-release antibacterial fiber membrane based on Janus structure was 73 μm, the thickness of the zein membrane was 179 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 278 μm. The elongation at break of the sustained-release antibacterial fiber membrane based on Janus structure was 56.3%, the breaking strength was 8.5 MPa, and the water vapor permeability was 8.5×10 -11 g / ms Pa, oxygen permeability is 7.4×10 -5 g / m 2 s, the colony count of Escherichia coli was 12 CFU, the colony count of Staphylococcus aureus was 11 CFU, the antibacterial rate of Escherichia coli was 98.29%, the antibacterial rate of Staphylococcus aureus was 98.61%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.12 L / cm 2 The release rate of curcumin in zein film was 0.07 L / cm 2 .
[0195] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0196] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0197] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber film based on the Janus structure is 12.77%, indicating that the slow-release antibacterial fiber film based on the Janus structure can reduce the water loss of fresh fruits and vegetables in the package, thereby delaying the water loss and maintaining freshness.
[0198] Example 4
[0199] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0200] (1) Preparation of raw materials;
[0201] β-cyclodextrin;
[0202] water;
[0203] Curcumin;
[0204] Ethanol;
[0205] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0206] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0207] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0208] Hexadecyltrimethylammonium bromide;
[0209] Metal salts: ferric chloride;
[0210] Precipitant: 1M ammonia water;
[0211] Dichloromethane;
[0212] N,N-dimethylformamide;
[0213] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0214] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 33° C. for 2 h, and then freezing centrifuging to obtain an inclusion complex powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion complex; wherein the molar ratio of curcumin to β-cyclodextrin is 0.972:1;
[0215] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid obtained in step (2.1) to an acetic acid aqueous solution with a volume concentration of 60%, and heating and stirring at 55° C. for 5 h to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid aqueous solution is 17%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 4%, the mass proportion of chitosan is 89%, and the mass proportion of the polylactic acid is 7%;
[0216] (3) preparing a zein spinning solution;
[0217] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 7, heating and stirring at 55° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 2%;
[0218] (4) preparing an aqueous solution of hexadecyltrimethylammonium bromide and an aqueous solution of negatively charged metal nanoparticles;
[0219] (4.1) preparing a hexadecyltrimethylammonium bromide aqueous solution;
[0220] Adding hexadecyltrimethylammonium bromide powder into water preheated to 50° C. and stirring until completely dissolved, thereby obtaining a hexadecyltrimethylammonium bromide aqueous solution with a concentration of 1 mM;
[0221] (4.2) preparing an aqueous solution of negatively charged metal nanoparticles;
[0222] The metal salt is dissolved in water at a mass ratio of 1:15, and then added to a precipitant to react at 70°C and 760 mmHg for 2 hours to form ferrite nanoparticles, and then cooled to 25°C and added to water, and finally ultrasonically treated to uniformly disperse the ferrite nanoparticles in water to obtain a negatively charged titanium dioxide nanoparticle aqueous solution with a mass fraction of 1%; wherein the mass ratio of the metal salt to the precipitant is 1:2;
[0223] (5) preparing a positively charged spinning solution A and a negatively charged spinning solution B;
[0224] Adding a hexadecyltrimethylammonium bromide aqueous solution to a zein spinning solution to obtain a positively charged spinning solution A; wherein the volume percentage of the hexadecyltrimethylammonium bromide aqueous solution relative to the zein spinning solution is 1.7%;
[0225] Adding a negatively charged metal nanoparticle aqueous solution to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a negatively charged spinning solution B; wherein the volume percentage of the negatively charged metal nanoparticle aqueous solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 1.7%;
[0226] (6) preparing chitosan / polylactic acid nanofiber membrane;
[0227] Chitosan and polylactic acid are added to a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a spinning solution, and a chitosan / polylactic acid nanofiber membrane is prepared by a double-needle parallel electrospinning method; wherein the mass ratio of chitosan to polylactic acid is 80:20; the total amount of chitosan and polylactic acid is 5% by mass / volume relative to the mixed solution of dichloromethane and N,N-dimethylformamide; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:3;
[0228] The electrospinning process parameters were: voltage 23 kV, needle gauge 22 G, distance between positive and negative electrodes 18 cm, spinning speed 1.8 mL / h, roller speed 200 rpm, spinning environment temperature 24 °C, and environment humidity 35% RH;
[0229] (7) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0230] The chitosan / polylactic acid nanofiber membrane obtained in step (6) is used as a receiving substrate, and the positively charged spinning solution A and the negatively charged spinning solution B obtained in step (4) are spun on both sides of the receiving substrate by a double-needle parallel electrospinning method to form a CUR@β-CD ICs / CS / PLA nanofiber membrane and a zein membrane, and then vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on a Janus structure; wherein the heat treatment temperature is 145° C. and the time is 15 min;
[0231] The spinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage 20 kV, needle gauge 20 G, distance between positive and negative electrodes 16 cm, spinning speed 0.8 mL / h, roller speed 200 rpm, spinning environment temperature 23 °C, and environment humidity 35% RH;
[0232] The spinning process parameters of the zein film are: voltage of 18 kV, needle specification of 20 G, distance between the positive electrode and the negative electrode of 20 cm, spinning speed of 0.9 mL / h, roller speed of 200 rpm, spinning environment temperature of 24 ° C, and environment humidity of 35% RH.
[0233] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the Janus structure-based sustained-release antibacterial fiber membrane was 64 μm, the thickness of the zein membrane was 171 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 265 μm. The elongation at break of the Janus structure-based sustained-release antibacterial fiber membrane was 58.6%, the breaking strength was 10.1 MPa, and the water vapor permeability was 7.4×10 -11 g / ms Pa, oxygen permeability is 8.1×10 -5 g / m 2 s, the colony count of Escherichia coli was 11 CFU, the colony count of Staphylococcus aureus was 15 CFU, the antibacterial rate of Escherichia coli was 98.43%, the antibacterial rate of Staphylococcus aureus was 98.1%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.15 L / cm 2 The release rate of curcumin in zein film was 0.08 L / cm 2 .
[0234] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0235] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0236] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber film based on the Janus structure is 15.42%, indicating that the slow-release antibacterial fiber film based on the Janus structure can reduce the loss of water in fresh fruits and vegetables in the package, thereby delaying the loss of water and maintaining freshness.
[0237] Example 5
[0238] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0239] (1) Preparation of raw materials;
[0240] β-cyclodextrin;
[0241] water;
[0242] Curcumin;
[0243] Ethanol;
[0244] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0245] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0246] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0247] Hexadecyltrimethylammonium bromide;
[0248] Metal salt: tetrabutyl titanate;
[0249] water;
[0250] Dichloromethane;
[0251] N,N-dimethylformamide;
[0252] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0253] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at 34° C. for 2 h, and then freezing centrifuging to obtain inclusion compound powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion compound; wherein the molar ratio of curcumin to β-cyclodextrin is 0.99:1;
[0254] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid prepared in step (2.1) to an acetic acid aqueous solution with a volume concentration of 60%, and heating and stirring at 60° C. for 5 h to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid aqueous solution is 18%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 3%, the mass proportion of chitosan is 88%, and the mass proportion of the polylactic acid is 9%;
[0255] (3) preparing a zein spinning solution;
[0256] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 7, heating and stirring at 60° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 4%;
[0257] (4) preparing an aqueous solution of hexadecyltrimethylammonium bromide and an aqueous solution of negatively charged metal nanoparticles;
[0258] (4.1) preparing a hexadecyltrimethylammonium bromide aqueous solution;
[0259] Adding hexadecyltrimethylammonium bromide powder into water preheated to 50° C. and stirring until completely dissolved, thereby obtaining a hexadecyltrimethylammonium bromide aqueous solution with a concentration of 1 mM;
[0260] (4.2) preparing an aqueous solution of negatively charged metal nanoparticles;
[0261] The metal salt is dissolved in water at a mass ratio of 1:15, and then reacted at 70°C and 760 mmHg for 2 hours to form titanium dioxide nanoparticles, which are then cooled to 25°C and added to water. Finally, the titanium dioxide nanoparticles are evenly dispersed in the water by ultrasonic treatment to obtain a 1% mass fraction of negatively charged titanium dioxide nanoparticles aqueous solution;
[0262] (5) preparing a positively charged spinning solution A and a negatively charged spinning solution B;
[0263] The hexadecyltrimethylammonium bromide aqueous solution is added to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a positively charged spinning solution A; wherein the volume percentage of the hexadecyltrimethylammonium bromide aqueous solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 2%;
[0264] Adding a negatively charged metal nanoparticle aqueous solution to a zein spinning solution to obtain a negatively charged spinning solution B; wherein the volume percentage of the negatively charged metal nanoparticle aqueous solution relative to the zein spinning solution is 2%;
[0265] (6) preparing chitosan / polylactic acid nanofiber membrane;
[0266] Chitosan and polylactic acid are added to a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a spinning solution, and a chitosan / polylactic acid nanofiber membrane is prepared by a double-needle parallel electrospinning method; wherein the mass ratio of chitosan to polylactic acid is 90:10; the total amount of chitosan and polylactic acid is 7% by mass / volume relative to the mixed solution of dichloromethane and N,N-dimethylformamide; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:3;
[0267] The electrospinning process parameters were: voltage 22 kV, needle gauge 22 G, distance between positive and negative electrodes 20 cm, spinning speed 1.7 mL / h, roller speed 200 rpm, spinning environment temperature 25 °C, and environment humidity 40% RH;
[0268] (7) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0269] The chitosan / polylactic acid nanofiber membrane obtained in step (6) is used as a receiving substrate, and the positively charged spinning solution A and the negatively charged spinning solution B obtained in step (4) are spun on both sides of the receiving substrate by a double-needle parallel electrospinning method to form a CUR@β-CD ICs / CS / PLA nanofiber membrane and a zein membrane, and then vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on a Janus structure; wherein the heat treatment temperature is 160° C. and the time is 15 min;
[0270] The spinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage 22 kV, needle gauge 20 G, distance between positive and negative electrodes 20 cm, spinning speed 1 mL / h, roller speed 200 rpm, spinning environment temperature 25 °C, and environment humidity 40% RH;
[0271] The spinning process parameters of the zein film are: voltage of 22 kV, needle specification of 20G, distance between the positive electrode and the negative electrode of 20 cm, spinning speed of 1 mL / h, roller speed of 200 rpm, spinning environment temperature of 25°C, and environment humidity of 40% RH.
[0272] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the Janus structure-based sustained-release antibacterial fiber membrane was 70 μm, the thickness of the zein membrane was 180 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 294 μm. The elongation at break of the Janus structure-based sustained-release antibacterial fiber membrane was 50.4%, the breaking strength was 8.2 MPa, and the water vapor permeability was 7.2×10 -11g / ms Pa, oxygen permeability is 7.5×10 -5 g / m 2 s, the colony count of Escherichia coli was 10 CFU, the colony count of Staphylococcus aureus was 12 CFU, the antibacterial rate of Escherichia coli was 98.57%, the antibacterial rate of Staphylococcus aureus was 98.29%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.11 L / cm 2 The release rate of curcumin in zein film was 0.06L / cm 2 .
[0273] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0274] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0275] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber film based on the Janus structure is 12.04%, indicating that the slow-release antibacterial fiber film based on the Janus structure can reduce the water loss of fresh fruits and vegetables in the package, thereby delaying the water loss and maintaining freshness.
[0276] Example 6
[0277] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0278] (1) Preparation of raw materials;
[0279] β-cyclodextrin;
[0280] water;
[0281] Curcumin;
[0282] Ethanol;
[0283] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0284] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0285] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0286] PEDOT:PSS: Manufacturer: Sane Chemical Technology (Shanghai) Co., Ltd., CAS No. 155090-83-8, Product No. A68291;
[0287] Zinc foil;
[0288] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0289] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 30° C. for 2.7 h, and then freezing centrifuging to obtain an inclusion compound powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion compound; wherein the molar ratio of curcumin to β-cyclodextrin is 0.95:1;
[0290] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid obtained in step (2.1) to an aqueous acetic acid solution with a volume concentration of 60%, and heating and stirring at 50°C for 6 hours to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid solution is 16%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 5%, the mass proportion of chitosan is 85%, and the mass proportion of the polylactic acid is 10%;
[0291] (3) preparing a zein spinning solution;
[0292] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 7, heating and stirring at 60° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 5%;
[0293] (4) preparing a positively charged spinning solution C and a positively charged spinning solution D;
[0294] (4.1) PEDOT:PSS powder was dissolved in water heated to 60°C by ultrasound to obtain a positively charged solution with a concentration of 1 mM;
[0295] (4.2) adding the positively charged solution obtained in step (4.1) to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a positively charged spinning solution C; wherein the volume percentage of the positively charged solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 1.5%;
[0296] (4.3) adding the positively charged solution obtained in step (4.1) to the zein spinning solution to obtain a positively charged spinning solution D; wherein the volume percentage of the positively charged solution relative to the zein spinning solution is 1.5%;
[0297] (5) Preparation of petal-shaped nano ZnO fiber membrane;
[0298] (5.1) Using 1M hydrochloric acid to treat a 1cm×1c m The zinc foil is cleaned to remove the passive oxidation layer on the zinc foil, and then fully cleaned with deionized water (DI);
[0299] (5.2) A 2M (NH4)2SO4 aqueous solution and a 0.1M ZnSO4 aqueous solution were stirred in a magnetic stirrer for 20 min to ensure uniform mixing, and then a 1M NaOH aqueous solution was added thereto and stirred for 10 min to a pH value of 7.5 to ensure that the electrodeposition process was in a slightly alkaline state, i.e., an electrolyte; wherein the mass ratio of (NH4)2SO4, ZnSO4 and NaOH was 16.4:1:2.5;
[0300] (5.3) The electrolyte was placed in an electrodeposition tank, and zinc foil was used as the working electrode and platinum rod was used as the counter electrode. The distance between the two electrodes was 1 cm. Finally, the deposited film was taken out of the bath, washed thoroughly with deionized water, and dried in a vacuum oven for 24 hours to obtain a petal-shaped nano ZnO fiber film. The current density of the electrodeposition was 0.5 A cm -2 ;
[0301] (6) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0302] Taking the petal-shaped nano ZnO fiber membrane as the receiving substrate, the positively charged spinning solution C and the positively charged spinning solution D were spun on both sides of the receiving substrate by needle-free electrospinning to form CUR@β-CD ICs / CS / PLA nanofiber membrane and zein membrane, and then vacuum dried, heat treated and cut to obtain the sustained-release antibacterial fiber membrane based on Janus structure; wherein the heat treatment temperature was 150℃ and the time was 15min;
[0303] The needleless electrospinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%;
[0304] The process parameters of needle-free electrospinning of zein film were as follows: the coil spinneret length was 20 cm, the diameter was 8 cm, the applied voltage was 55 kV, the distance between the coil spinnerets was set to 10 cm, the collection distance was set to 25 cm, and the line speed was 0.2 m min -1 , the coil speed was 15 rpm, the spinning zone temperature was room temperature, and the humidity was maintained at 30 RH%.
[0305] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the Janus structure-based sustained-release antibacterial fiber membrane was 68 μm, the thickness of the zein membrane was 153 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 237 μm. The elongation at break of the Janus structure-based sustained-release antibacterial fiber membrane was 53.2%, the breaking strength was 8.3 MPa, and the water vapor permeability was 7.9×10 -11 g / ms Pa, oxygen permeability is 7.6×10 -5 g / m 2 s, the colony count of Escherichia coli was 10 CFU, the colony count of Staphylococcus aureus was 8 CFU, the antibacterial rate of Escherichia coli was 98.57%, the antibacterial rate of Staphylococcus aureus was 98.99%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.13 nL / cm 2 The release rate of curcumin in zein film was 0.08nL / cm 2 .
[0306] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0307] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0308] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber membrane based on the Janus structure is 13%, indicating that the slow-release antibacterial fiber membrane based on the Janus structure can reduce the water loss of fresh fruits and vegetables in the package, thereby delaying the water loss and maintaining freshness.
[0309] Example 7
[0310] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0311] (1) Preparation of raw materials;
[0312] β-cyclodextrin;
[0313] water;
[0314] Curcumin;
[0315] Ethanol;
[0316] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56 H 103 N9O 39 ;
[0317] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0318] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0319] PEDOT:PSS: Manufacturer: Sane Chemical Technology (Shanghai) Co., Ltd., CAS No. 155090-83-8, Product No. A68291;
[0320] Zinc foil;
[0321] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0322] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 32° C. for 2 h, and then freezing centrifuging to obtain an inclusion compound powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion compound; wherein the molar ratio of curcumin to β-cyclodextrin is 0.98:1;
[0323] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid obtained in step (2.1) to an acetic acid aqueous solution with a volume concentration of 60%, and heating and stirring at 55° C. for 4 h to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid solution is 18%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 5%, the mass proportion of chitosan is 90%, and the mass proportion of the polylactic acid is 5%;
[0324] (3) preparing a zein spinning solution;
[0325] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 6, heating and stirring at 50° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 3%;
[0326] (4) preparing a positively charged spinning solution C and a positively charged spinning solution D;
[0327] (4.1) PEDOT:PSS powder was dissolved in water heated to 60°C by ultrasound to obtain a positively charged solution with a concentration of 1 mM;
[0328] (4.2) adding the positively charged solution obtained in step (4.1) to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a positively charged spinning solution C; wherein the volume percentage of the positively charged solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 1%;
[0329] (4.3) adding the positively charged solution obtained in step (4.1) to the zein spinning solution to obtain a positively charged spinning solution D; wherein the volume percentage of the positively charged solution relative to the zein spinning solution is 1.7%;
[0330] (5) Preparation of petal-shaped nano ZnO fiber membrane;
[0331] (5.1) Using 1M hydrochloric acid to treat a 1cm×1c m The zinc foil is cleaned to remove the passive oxidation layer on the zinc foil, and then fully cleaned with deionized water (DI);
[0332] (5.2) A 2M (NH4)2SO4 aqueous solution and a 0.1M ZnSO4 aqueous solution were stirred in a magnetic stirrer for 20 min to ensure uniform mixing, and then a 1M NaOH aqueous solution was added thereto and stirred for 10 min to a pH value of 8 to ensure that the electrodeposition process was in a slightly alkaline state, i.e., an electrolyte; wherein the mass ratio of (NH4)2SO4, ZnSO4 and NaOH was 16.4:1:2.5;
[0333] (5.3) The electrolyte was placed in an electrodeposition tank, and zinc foil was used as the working electrode and platinum rod was used as the counter electrode. The distance between the two electrodes was 1 cm. Finally, the deposited film was taken out of the bath, washed thoroughly with deionized water, and dried in a vacuum oven for 24 hours to obtain a petal-shaped nano ZnO fiber film. The current density of the electrodeposition was 0.5 A cm -2 ;
[0334] (6) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0335] Taking the petal-shaped nano ZnO fiber membrane as the receiving substrate, the positively charged spinning solution C and the positively charged spinning solution D were spun on both sides of the receiving substrate by the double-needle parallel electrospinning method to form CUR@β-CD ICs / CS / PLA nanofiber membrane and zein membrane, and then vacuum dried, heat treated and cut to obtain the sustained-release antibacterial fiber membrane based on Janus structure; wherein the heat treatment temperature was 120℃ and the time was 10min;
[0336] The spinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage 22 kV, needle gauge 20 G, distance between positive and negative electrodes 18 cm, spinning speed 0.8 mL / h, roller speed 200 rpm, spinning environment temperature 22 °C, and environment humidity 30% RH;
[0337] The spinning process parameters of the zein film are: voltage of 16 kV, needle specification of 20 G, distance between the positive electrode and the negative electrode of 15 cm, spinning speed of 0.5 mL / h, roller speed of 200 rpm, spinning environment temperature of 22° C., and environment humidity of 30% RH.
[0338] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the Janus structure-based sustained-release antibacterial fiber membrane was 65 μm, the thickness of the zein membrane was 135 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 218 μm. The elongation at break of the Janus structure-based sustained-release antibacterial fiber membrane was 55.7%, the breaking strength was 7.8 MPa, and the water vapor permeability was 8.2×10 -11 g / ms Pa, oxygen permeability is 6.8×10 -5 g / m 2 s, the colony count of Escherichia coli was 13 CFU, the colony count of Staphylococcus aureus was 10 CFU, the antibacterial rate of Escherichia coli was 98.14%, the antibacterial rate of Staphylococcus aureus was 98.74%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.15 nL / cm 2 The release rate of curcumin in zein film was 0.12nL / cm 2 .
[0339] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0340] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0341] From the above test, it can be seen that the weight loss rate of potatoes preserved by the slow-release antibacterial fiber membrane based on the Janus structure is 12%, indicating that the slow-release antibacterial fiber membrane based on the Janus structure can reduce the water loss of fresh fruits and vegetables in the package, thereby delaying the water loss and maintaining freshness.
[0342] Example 8
[0343] A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, comprising the following steps:
[0344] (1) Preparation of raw materials;
[0345] β-cyclodextrin;
[0346] water;
[0347] Curcumin;
[0348] Ethanol;
[0349] Chitosan: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., CAS number is 9012-76-4, molecular formula is C 56H 103 N9O 39 ;
[0350] Polylactic acid: manufacturer is Roen Reagent Network, CAS number is 2610-05-16, weight average molecular weight is 80000;
[0351] Zein: The manufacturer is Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number is 9010-66-6, and the product number is BD157001;
[0352] PEDOT:PSS: Manufacturer: Sane Chemical Technology (Shanghai) Co., Ltd., CAS No. 155090-83-8, Product No. A68291;
[0353] Zinc foil;
[0354] (2) Preparation of CUR@β-CD ICs / CS / PLA spinning solution;
[0355] (2.1) dissolving β-cyclodextrin in water to prepare a β-cyclodextrin aqueous solution with a concentration of 1 wt%, dissolving curcumin in ethanol to prepare a curcumin ethanol solution with a concentration of 10 mg / mL, then adding the curcumin ethanol solution to the β-cyclodextrin aqueous solution, stirring at a temperature of 35° C. for 2.5 h, and then freezing centrifuging to obtain an inclusion complex powder, washing away excess impurities, and obtaining a curcumin / β-cyclodextrin inclusion complex; wherein the molar ratio of curcumin to β-cyclodextrin is 1.02:1;
[0356] (2.2) adding the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid obtained in step (2.1) to an aqueous acetic acid solution with a volume concentration of 60%, and heating and stirring at 60°C for 5 hours to obtain a CUR@β-CD ICs / CS / PLA spinning solution; wherein the total amount of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid relative to the mass / volume percentage of the acetic acid solution is 20%, and based on the total mass of the curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of the curcumin / β-cyclodextrin inclusion complex is 2%, the mass proportion of chitosan is 90%, and the mass proportion of the polylactic acid is 8%;
[0357] (3) preparing a zein spinning solution;
[0358] Adding zein to an aqueous solution of acetic acid with a volume fraction of 70%, adjusting the pH value to 5, heating and stirring at 55° C. for 1 hour, to obtain a zein spinning solution; wherein the mass / volume percentage of zein relative to the acetic acid solution is 1%;
[0359] (4) preparing a positively charged spinning solution C and a positively charged spinning solution D;
[0360] (4.1) PEDOT:PSS powder was dissolved in water heated to 60°C by ultrasound to obtain a positively charged solution with a concentration of 1 mM;
[0361] (4.2) adding the positively charged solution obtained in step (4.1) to the CUR@β-CD ICs / CS / PLA spinning solution to obtain a positively charged spinning solution C; wherein the volume percentage of the positively charged solution relative to the CUR@β-CD ICs / CS / PLA spinning solution is 2%;
[0362] (4.3) adding the positively charged solution obtained in step (4.1) to the zein spinning solution to obtain a positively charged spinning solution D; wherein the volume percentage of the positively charged solution relative to the zein spinning solution is 2%;
[0363] (5) Preparation of petal-shaped nano ZnO fiber membrane;
[0364] (5.1) Using 1M hydrochloric acid to treat a 1cm×1c m The zinc foil is cleaned to remove the passive oxidation layer on the zinc foil, and then fully cleaned with deionized water (DI);
[0365] (5.2) A 2M (NH4)2SO4 aqueous solution and a 0.1M ZnSO4 aqueous solution were stirred in a magnetic stirrer for 20 min to ensure uniform mixing, and then a 1M NaOH aqueous solution was added thereto and stirred for 10 min to a pH value of 9.5 to ensure that the electrodeposition process was in a slightly alkaline state, i.e., an electrolyte; wherein the mass ratio of (NH4)2SO4, ZnSO4 and NaOH was 16.4:1:2.5;
[0366] (5.3) The electrolyte was placed in an electrodeposition tank, and zinc foil was used as the working electrode and platinum rod was used as the counter electrode. The distance between the two electrodes was 1 cm. Finally, the deposited film was taken out of the bath, washed thoroughly with deionized water, and dried in a vacuum oven for 24 hours to obtain a petal-shaped nano ZnO fiber film. The current density of the electrodeposition was 0.5 A cm -2 ;
[0367] (6) Preparation of sustained-release antibacterial fiber membrane based on Janus structure;
[0368] Taking the petal-shaped nano ZnO fiber membrane as the receiving substrate, the positively charged spinning solution C and the positively charged spinning solution D were spun on both sides of the receiving substrate by the double-needle parallel electrospinning method to form CUR@β-CD ICs / CS / PLA nanofiber membrane and zein membrane, and then vacuum dried, heat treated and cut to obtain the sustained-release antibacterial fiber membrane based on Janus structure; wherein the heat treatment temperature was 160℃ and the time was 13min;
[0369] The spinning process parameters of CUR@β-CD ICs / CS / PLA nanofiber membrane were as follows: voltage 16 kV, needle gauge 20 G, distance between positive and negative electrodes 15 cm, spinning speed 0.5 mL / h, roller speed 200 rpm, spinning environment temperature 24 °C, and ambient humidity 28% RH;
[0370] The spinning process parameters of the zein film are: voltage of 18 kV, needle specification of 20 G, distance between the positive electrode and the negative electrode of 20 cm, spinning speed of 0.8 mL / h, roller speed of 200 rpm, spinning environment temperature of 25 ° C, and environment humidity of 28% RH.
[0371] The thickness of the CUR@β-CD ICs / CS / PLA nanofiber membrane in the sustained-release antibacterial fiber membrane based on Janus structure was 80 μm, the thickness of the zein membrane was 186 μm, and the thickness of the chitosan / polylactic acid nanofiber membrane was 275 μm. The elongation at break of the sustained-release antibacterial fiber membrane based on Janus structure was 52.4%, the breaking strength was 9.2 MPa, and the water vapor permeability was 7.5×10 -11 g / ms Pa, oxygen permeability is 7.4×10 -5 g / m 2 s, the colony count of Escherichia coli was 12 CFU, the colony count of Staphylococcus aureus was 11 CFU, the antibacterial rate of Escherichia coli was 98.29%, the antibacterial rate of Staphylococcus aureus was 98.61%, and the release amount of curcumin in CUR@β-CD ICs / CS / PLA nanofiber membrane was 0.11 nL / cm 2 The release rate of curcumin in zein film was 0.1nL / cm 2 .
[0372] The slow-release antibacterial fiber membrane based on Janus structure prepared above can be used for food preservation.
[0373] To verify the preservation performance of the sustained-release antibacterial fiber membrane based on the Janus structure, fresh potatoes were first cut into a size of 3cm×1cm×3cm, then pretreated under ultraviolet light for 1h, and then packaged using the sustained-release antibacterial fiber membrane based on the Janus structure and stored at room temperature for 4 days.
[0374] From the above test, it can be seen that the weight loss rate of potatoes preserved using the slow-release antibacterial fiber film based on the Janus structure is 15%, indicating that the slow-release antibacterial fiber film based on the Janus structure can reduce the water loss of fresh fruits and vegetables in the package, thereby delaying the water loss and maintaining freshness.
Claims
1. A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, characterized in that: Chitosan / polylactic acid nanofiber membrane is used as a receiving substrate, and a double-needle parallel electrospinning method or a needle-free electrospinning method is used to spin a positively charged spinning solution A and a negatively charged spinning solution B to obtain an electrospun fiber membrane. The electrospun fiber membrane is vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on a Janus structure. The positively charged spinning solution A is obtained by adding the positively charged solution to the CUR@β-CD ICs / CS / PLA spinning solution, and the negatively charged spinning solution B is obtained by adding the negatively charged solution to the zein spinning solution; or, the positively charged spinning solution A is obtained by adding the positively charged solution to the zein spinning solution, and the negatively charged spinning solution B is obtained by adding the negatively charged solution to the CUR@β-CD ICs / CS / PLA spinning solution; The CUR@β-CDICs / CS / PLA spinning solution is obtained by dissolving curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid in a solvent.
2. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 1, characterized in that: The specific preparation process of CUR@β-CDICs / CS / PLA spinning solution is as follows: curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid are added to an acetic acid solution with a volume concentration of 60%, and heated and stirred at 50-60°C for 4-6h to obtain CUR@β-CD ICs / CS / PLA spinning solution; The total amount of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid is 16-20% by mass / volume relative to the acetic acid solution; based on the total mass of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of curcumin / β-cyclodextrin inclusion complex is 2-5%, the mass proportion of chitosan is 85-90%, and the mass proportion of polylactic acid is 5-10%.
3. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 1, characterized in that: The specific preparation process of the zein spinning solution is as follows: adding zein to an acetic acid solution with a volume fraction of 70%, adjusting the pH value to 5-7, heating and stirring at 50-60° C. for 1 hour, and obtaining the zein spinning solution; The mass / volume percentage of zein relative to the acetic acid solution is 1-5%.
4. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 1, characterized in that: The specific preparation process of chitosan / polylactic acid nanofiber membrane is as follows: chitosan and polylactic acid are added to a mixed solution of dichloromethane and N,N-dimethylformamide to obtain a spinning solution, and the chitosan / polylactic acid nanofiber membrane is prepared by an electrospinning method; The mass ratio of chitosan to polylactic acid is 70-90:10-30; the mass / volume percentage of the total amount of chitosan and polylactic acid relative to the mixed solution of dichloromethane and N,N-dimethylformamide is 5-7%; in the mixed solution of dichloromethane and N,N-dimethylformamide, the volume ratio of dichloromethane to N,N-dimethylformamide is 7:
3.
5. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 1, characterized in that: The positively charged solution was a 1 mM hexadecyltrimethylammonium bromide aqueous solution; The negatively charged solution is an aqueous solution of negatively charged metal nanoparticles; the mass fraction of the aqueous solution of negatively charged metal nanoparticles is 1%; the metal nanoparticles are gold nanoparticles, silver nanoparticles, zinc oxide nanoparticles, ferrite nanoparticles or titanium dioxide nanoparticles; The volume percentage of the positively charged solution or the negatively charged solution relative to the CUR@β-CD ICs / CS / PLA spinning solution or the zein spinning solution is 1-2%.
6. A method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure, characterized in that: Taking the petal-shaped nano ZnO fiber membrane as the receiving substrate, the positively charged spinning solution C and the positively charged spinning solution D are spun together to obtain the electrospun fiber membrane by using the double-needle parallel electrospinning or needle-free electrospinning method. The electrospun fiber membrane is vacuum dried, heat treated, and cut to obtain a sustained-release antibacterial fiber membrane based on the Janus structure. The petal-shaped nano ZnO fiber membrane is prepared by electrochemical deposition method using zinc foil as substrate; The electrolyte used in electrochemical deposition is a mixture of (NH4)2SO4 solution, ZnSO4 solution and NaOH solution, and the pH value of the electrolyte is 7.5 to 9.5; The positively charged spinning solution C was obtained by adding the positively charged solution to the CUR@β-CD ICs / CS / PLA spinning solution, and the positively charged spinning solution D was obtained by adding the positively charged solution to the zein spinning solution; the CUR@β-CDICs / CS / PLA spinning solution was obtained by dissolving curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid in a solvent.
7. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 6, characterized in that: The specific preparation process of CUR@β-CDICs / CS / PLA spinning solution is as follows: curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid are added to an acetic acid solution with a volume concentration of 60%, and heated and stirred at 50-60°C for 4-6h to obtain CUR@β-CD ICs / CS / PLA spinning solution; The total amount of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid is 16-20% by mass / volume relative to the acetic acid solution; based on the total mass of curcumin / β-cyclodextrin inclusion complex, chitosan and polylactic acid, the mass proportion of curcumin / β-cyclodextrin inclusion complex is 2-5%, the mass proportion of chitosan is 85-90%, and the mass proportion of polylactic acid is 5-10%.
8. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 6, characterized in that: The specific preparation process of the zein spinning solution is as follows: adding zein to an acetic acid solution with a volume fraction of 70%, adjusting the pH value to 5-7, heating and stirring at 50-60° C. for 1 hour, and obtaining the zein spinning solution; The mass / volume percentage of zein relative to the acetic acid solution is 1-5%.
9. The method for preparing a sustained-release antibacterial fiber membrane based on a Janus structure according to claim 6, characterized in that: The positively charged solution was a 1 mM solution obtained by dissolving PEDOT:PSS powder in water; The volume percentage of the positively charged solution relative to the CUR@β-CD ICs / CS / PLA spinning solution or the zein spinning solution is 1-2%.
10. Application of the sustained-release antibacterial fiber membrane based on Janus structure obtained by the preparation method according to any one of claims 1 to 9, characterized in that: Used for food preservation.
Citation Information
Patent Citations
Chitosan / zein slow-release antibacterial film with Janus structure as well as preparation method and application of chitosan / zein slow-release antibacterial film
CN117924779A
Zinc oxide powder with flower-like micro-nano structure as well as preparation method and application thereof
CN109928421A
Electrostatic spinning film as well as preparation method thereof and application thereof in salinity gradient energy power generation
CN109957885A
Preparation method of protective material for efficiently adsorbing viruses
CN111893650A
Environment-friendly antibacterial colored polylactic acid fiber and preparation method thereof
CN115821424A